2018
DOI: 10.1016/j.jhep.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus reinfection after successful treatment with direct-acting antiviral therapy in a large population-based cohort

Abstract: Direct-acting antivirals are an effective tool for the treatment of hepatitis C virus, enabling the elimination of the virus. However, some patients who have been successfully treated with direct-acting antivirals are at risk of reinfection. Our findings showed that the risk of reinfection was highest among people with recent injection drug use. Among people who inject drugs, daily use of opioid-agonist therapy was associated with a lower risk of reinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
87
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 40 publications
7
87
0
2
Order By: Relevance
“…Although, it has been shown that IDU and OST could significantly reduce the SVR, in our study these factors were not associated with treatment effectiveness. In a recent study, it has been shown that reinfection rate is higher among recent IDU compared to past IDU . In the current study, in the LDV/SOF ± RBV multivariable model; after adjusting for other characteristics, past IDU and OST were significantly associated with higher SVR achievement (Figure ).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Although, it has been shown that IDU and OST could significantly reduce the SVR, in our study these factors were not associated with treatment effectiveness. In a recent study, it has been shown that reinfection rate is higher among recent IDU compared to past IDU . In the current study, in the LDV/SOF ± RBV multivariable model; after adjusting for other characteristics, past IDU and OST were significantly associated with higher SVR achievement (Figure ).…”
Section: Discussionsupporting
confidence: 48%
“…In a recent study, it has been shown that reinfection rate is higher among recent IDU compared to past IDU. 28,45 In the current study, in the LDV/SOF ± RBV multivariable model; after adjusting for other characteristics, past IDU and OST were significantly associated with higher SVR achievement ( Figure 2). This finding highlights the need for harm reduction services and OST programmes among current IDUs.…”
Section: Yesmentioning
confidence: 60%
“…Data on reinfection in the DAA era are emerging. We have recently shown that recent PWID had higher reinfection rates compared to past PWID and those not injecting . In the current study, some individuals who had a positive RNA test following a negative test while on treatment or soon after the end of treatment followed by a positive RNA test before or at 10 weeks after the end of treatment are considered to have failed treatment.…”
Section: Discussionmentioning
confidence: 78%
“…27 In a large population-based cohort (British Columbia Hepatitis Testers Cohort) enrolling 4114 individuals, 40 subjects experienced an HCV re-infection. 28 Moreover, our population was at low probability of re-infection, since the presumed duration of HCV infection was very long (at least 12 years). Instead, patient #6 harboured different HCV 1 subgenotypes (1b and 1a respectively) before the start of the DAA regimen and at relapse; therefore, in this case, we can hypothesize a re-infection with another subgenotype of HCV, although an erroneous identification of the HCV subgenotype before the start of DAA may also be possible.…”
Section: Discussionmentioning
confidence: 92%
“…In a large French AIDS cohort on 3406 patients, HCV re‐infections occurred in 73 with an incidence of 2.52%‐2.90% patients‐year . In a large population‐based cohort (British Columbia Hepatitis Testers Cohort) enrolling 4114 individuals, 40 subjects experienced an HCV re‐infection . Finally, of great interest were the results of a meta‐analysis evaluating the risk of late relapse or HCV re‐infection after achieving a sustained virological response: in the 43 studies evaluating 7969 HCV‐monoinfected patients, the pooled recurrence rate was 1.85/1000 events/person per year of follow‐up (PYFU; 95% confidence interval [CI]: 71‐3.35); in the 14 studies evaluating 771 HCV‐monoinfected “high‐risk” patients (intravenous drug users or prisoners), the pooled recurrence rate was 22.32/1000 PYFU (95% CI, 13.07‐33.46); in the four studies evaluating 309 HIV/HCV coinfected patients, the pooled recurrence rate was 32.02/1000 PYFU (95% CI, 0.00‐123.49) …”
Section: Discussionmentioning
confidence: 99%